EAPH-10. SUCCESSFUL TREATMENT OF A SECONDARY PEDIATRIC HIGH GRADE GLIOMA WITH A NOVEL BEND4-NTRK2 FUSION WITH ENTRECTINIB, A TRK INHIBITOR. Issue 2 (22nd June 2018) - Felker, James; Philbrook, Bryan; Schneiderjan, Matthew; Chern, Joshua; Mazewski, Claire; Eaton, Bree; Chow-Maneval, Edna; MacDonald, Tobey; Aguilera, Dolly
Abstract: A 2 month old child with a large hemispheric tumor; after subtotal resection, pathology showed pilomyxoid astrocytoma with BRAFV600E mutation by immunohistochemistry and pyrosequencing. He had multiple episodes of radiographic and clinical progression. Over the course of 5 years, therapy included carboplatin, TPCV, velban, and immunotherapy. Vemurafenib and dabrafenib were administered with no response. MRI showed rapid tumor progression in the brain with spinal dissemination and significant clinical deterioration. Patient underwent tumor debulking and pathology confirmed a high grade astrocytoma, without BRAF V600E mutation, but with a novel BEND4-NTRK2 fusion by molecular genetic testing. He underwent whole brain radiation of 33 Gy in 16 fractions and boost to primary tumor bed to a total dose of 43 Gy. No radiation was given to the spine. One month later, patient started compassionate treatment with entrectinib, a novel, CNS-active, TRK inhibitor, at 400 mg/m2/day. MRI obtained after 28 days on treatment demonstrated significant radiographic regression, with rapid improvement in clinical symptoms. His dose was then increased to 550 mg/m2/day. After 2 additional cycles, the tumor continues to decrease in size in the brain and a spine MRI demonstrated complete response despite no radiation to the spine. Toxicities included Grade 1 ALT, cholesterol and peripheral edema. In summary, we report the case of a refractory BRAF V600E mutated low grade glioma transformed into a high grade with a novel BEND4-NTRK2 fusion, and profound radiographic and clinical response to entrectinib.